2013
DOI: 10.1111/bcpt.12145
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin Complex ContainingLippia grataLeaf Essential Oil Reduces Orofacial Nociception in Mice - Evidence of Possible Involvement of Descending Inhibitory Pain Modulation Pathway

Abstract: The treatment of orofacial pain remains a major challenge for modern medicine. Thus, we prepared and physicochemically characterized a new b-cyclodextrin complex containing Lippia grata leaf essential oil (b-CD/EO) to investigate their possible antinociceptive activity in animal models of orofacial pain. The results of Differential scanning calorimeter (DSC) and Thermogravimetry/derivative thermogravimetry (TG/DTG) showed that the products prepared by Slurry complexation (SC) method were able to incorporate gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…In addition, it has been suggested that the association of natural products with preventive care can reduce the high incidence of diseases that affect the dental element as the periodontal disease (Juiz et al, 2010;Siqueira et al, 2010;Guimarães et al, 2013). Recently, our group has developing study about the pharmacological use of natural products, as medicinal plants, to treat orofacial disroders Bonjardim et al, 2011;Siqueira-Lima et al, 2014;Quintans et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been suggested that the association of natural products with preventive care can reduce the high incidence of diseases that affect the dental element as the periodontal disease (Juiz et al, 2010;Siqueira et al, 2010;Guimarães et al, 2013). Recently, our group has developing study about the pharmacological use of natural products, as medicinal plants, to treat orofacial disroders Bonjardim et al, 2011;Siqueira-Lima et al, 2014;Quintans et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics of CDs are interesting in relation to complex compounds, such as terpenes, that present many limitations due to their low solubility in an aqueous medium (Quintans-Júnior et al, 2016;Siqueira-Lima et al, 2014). CDs are usually able to enhance the bioavailability of insoluble compounds by increasing their drug solubility, their dissolution, and their drug permeability (Rasheed & Kumar, 2008).…”
Section: Inclusion Methods and Complexation Efficiencymentioning
confidence: 99%
“…However, this does not appear to be feasible for all non-polar compounds due to the different complexation rates of major compounds. A better complexation with CDs is usually found with compounds and/or active substances from essential oils Pinho, Grootveld, Soares & Henriques, 2014a;Siqueira-Lima et al, 2014).…”
Section: Inclusion Methods and Complexation Efficiencymentioning
confidence: 99%
See 2 more Smart Citations